2020
DOI: 10.1186/s12882-020-01794-w
|View full text |Cite
|
Sign up to set email alerts
|

Timing of kidney biopsy in type 2 diabetic patients: a stepwise approach

Abstract: Background: Diabetic nephropathy (DN) is the most prevalent cause of renal disease in type 2 diabetic patients and is usually diagnosed clinically. A kidney biopsy is considered when non-diabetic renal disease (NDRD) is suspected, such as rapid progression in renal function impairment and severe proteinuria. Still, there is yet no consensus on the timing of kidney biopsy in type 2 diabetic patients. This study aims to identify markers that can help differentiate between DN and NDRD and guide the decision of ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 46 publications
6
14
2
Order By: Relevance
“…In our study, as previously reported studies, initial proteinuria 28,30 serum albumin 19,31,32 serum glucose 33 , HbA1C 28,32,34 were not different in DN and NDKD patients. Similar to Liu et al 34 , our DN patients had lower serum hemoglobin levels.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, as previously reported studies, initial proteinuria 28,30 serum albumin 19,31,32 serum glucose 33 , HbA1C 28,32,34 were not different in DN and NDKD patients. Similar to Liu et al 34 , our DN patients had lower serum hemoglobin levels.…”
Section: Discussionsupporting
confidence: 88%
“…In type 2 DM, the onset of the disease is difficult to detect, so it is recommended to investigate for DN at the time of diagnosis 26 . As in our study, the incidence of NDKD increased in patients with short diabetes duration [27][28][29] .…”
Section: Discussionsupporting
confidence: 81%
“…In our study, as previously reported studies, initial proteinuria 28,30 serum albumin 19,31,32 serum glucose, 33 HbA1C 28,32,34 were not different in DN and NDKD patients. Similar to Liu et al, 34 our DN patients had lower serum hemoglobin levels.…”
Section: Discussionsupporting
confidence: 88%
“…In type 2 DM, the onset of the disease is difficult to detect, so it is recommended to investigate for DN at the time of diagnosis 26 . As in our study, the incidence of NDKD increased in patients with short diabetes duration 27‐29 …”
Section: Discussionsupporting
confidence: 78%
“…Due to its indolent nature, chronic kidney disease diagnosed after DR is typically presumed to be DN [5]. However, diabetic patients with high amounts of proteinuria without DR are recommended for a kidney biopsy to rule out other glomerular diseases [13][14][15][16]. Because frequent complications from kidney biopsy often occur, many patients may refuse to receive one.…”
Section: Introductionmentioning
confidence: 99%